2019
DOI: 10.1590/1807-3107bor-2019.vol33.0009
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between try-in pastes and resin cements, and color stability of bonded lithium disilicate disks

Abstract: Rafael Soares DINIZ (a) Letícia Fecury Bogéa de ALBUQUERQUE (a) Rudys de Jesus Rodolfo TAVAREZ (a) Eduardo Buozzi MOFFA (a) Andréa Dias Neves LAGO (b) Letícia Machado GONÇALVES (a) Correspondence between try-in pastes and resin cements, and color stability of bonded lithium disilicate disks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It was concluded that both the white and clear resin cement shade groups could not mask the dark background. Those results were similar to the study of Yıldırım et al 8 Diniz et al 14 examined the colour agreement between Variolink Veneer and Allcem Veneer resin cement and try-in pastes in 1.0 and 0.5 mm thickness lithium disilicate specimens and found colour correspondence in the 1.0 mm ceramic specimens for the Variolink Veneer and Allcem Veneer systems. Mourouzis et al 24 investigated the color agreement between Variolink Veneer and Variolink Esthetic LC resin cement and try-in pastes on lithium disilicate material, and they concluded that significant colour differences were found between resin cements and their corresponding try-in pastes.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…It was concluded that both the white and clear resin cement shade groups could not mask the dark background. Those results were similar to the study of Yıldırım et al 8 Diniz et al 14 examined the colour agreement between Variolink Veneer and Allcem Veneer resin cement and try-in pastes in 1.0 and 0.5 mm thickness lithium disilicate specimens and found colour correspondence in the 1.0 mm ceramic specimens for the Variolink Veneer and Allcem Veneer systems. Mourouzis et al 24 investigated the color agreement between Variolink Veneer and Variolink Esthetic LC resin cement and try-in pastes on lithium disilicate material, and they concluded that significant colour differences were found between resin cements and their corresponding try-in pastes.…”
Section: Discussionsupporting
confidence: 87%
“…These differences may have occurred due to the presence of particular components, fillers and pigments in the ceramic type and the absence of a polymerization process in the try-in paste. 3,14 Many commonly used dual-polymerizing resin cement systems contain benzoyl peroxide/tertiary amines, which act as autopolymerization initiators and are responsible for colour changes due to the oxidation reaction during autopolymerization. 23,26 Therefore, dual-polymerizing resin cement systems including an amine-free redox initiator have been developed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations